Difusi Teknologi Pembuatan Pupuk Cair Organik menggunakan Starter Lokal - Isdiana Suprapti; Kelik Perdana Windra Sukma (Universitas Pahlawan Tuanku Tambusai, 2022)
One of the ways to increase agricultural production is by improved cultivation techniques through soil fertility management. The balance of soil fertility both chemically, physically and biologically can be restored by using organic fertilizers. Farmers in Sopa'ah Village, Pademawu District, Pamekasan Regency generally use inorganic fertilizers in the cultivation of rice and corn. This farmer had received training on the manufacture of organic fertilizer but it was not continued because it was constrained by the availability of EM4 as a starter. This service aims to teach farmers about the principles of making starter and liquid organic fertilizer (LOF). The service is in the form of training which was held in two parts, the manufacture of starter and the manufacture of liquid organic fertilizer using local materials. After the training, farmers were able to understand and practice the manufacture of starter and liquid organic fertilizer. Farmers are expected to be able to apply the LOF so as to increase soil fertility and crop production. The resulting POC is expected to be commercialized to increase farmers' income.